Datas em Questão. Problemas de Três epígrafes funerárias de Vilar de Frades - Faure, Francisco G. C. Líbano Monteiro (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
After a comparison of the dates engraved on some flagstones from the church of the Monastery of S. Salvador de Vilar de Frades (Barcelos, Portugal) with the known dates of death of the persons that should be buried in such graves, it is possible to verify an inconsistency between each pair of dates. In this paper we try to understand this inconsistency advancing the hypothesis that this particular kind of tumular inscriptions served more as a way to identify the ownership of the grave than to identify the persons buried in there.